Social sciences in the transdisciplinary making of sustainable artifacts - Nascimento, S.; Pólvora, A. (Social Science Information, 2016)
From a transdisciplinary standpoint, we need to address the environmental, economic, social and cultural dimensions of sustainability by calling attention to the key role of social sciences in working with other experts and in engaging stakeholders. This article is focused on present and potential direct contributions from social scientists in the practical realms of designing, producing and using sustainable technologies, while also arguing that more active interventions are not only desirable, but considerably urgent from start to end in these realms. In addition, we argue that such interventions are now facing promising opportunities with upcoming technological trends that range from open design and new maker cultures to rapid prototyping or digital fabrication. These trends already offer several openness routes in technology creation, and consequently foster wider practical and conceptual transdisciplinary platforms to envision, build and share not only physical objects but also the ideas and discussions that constitute them.